(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This research studies the asymptotic structures of Banach spaces through the notion of envelope functions. Analogous to the original ones, a new notion of disjoint-envelope functions is introduced and the properties of these functions in connection to the asymptotic structures are studied. The main result gives a new characterization of asymptotic- spaces in terms of the -behavior of disjoint-permissible vectors of constant coefficients.